Assessment of mechanical properties and durability of compressed mud bricks stabilized with stone dust, wheat straw, and cement - Yaqin Chen; Muhammad Saqib; Khan Shahzada; Mohammad Aizaz; Akhtar Gul (Scientific Reports)
Abstract For millennia mud has been utilized to make brick for the construction of both residential as well as architectural purposes. However, concerns regarding their vulnerability to different kinds of hazards due to their weak mechanical properties and durability have emerged. This study addressed the global challenge of developing sustainable and affordable construction materials, particularly in resource-constrained regions. This research aim was to enhance the mechanical properties and durability of compressed mud bricks through a partial replacement technique by incorporating locally available materials like stone dust, wheat straw, and cement. A total of nine combinations were studied. Stone dust was used as 10%, 20%, and 30% by weight. Wheat straw was used in 0.5%, 1%, and 1.5% by weight. Cement was added in a fixed amount of 5% by weight throughout. Among the nine combinations, the one showing maximum compressive strength and minimum water absorption for unit brick was selected for further study. For comparison purposes, control mix samples (including 5% of cement) were also prepared. The combination selected after the tests was 20% stone dust, 0.5% wheat straw, and 5% cement. The selected combination and control mix compressed mud bricks were further evaluated through various tests such as flexural strength test on unit brick, water jet test on unit brick, compression strength test on masonry prism, triplet test, and diagonal shear test on masonry wallet was carried out. The increase in compressive strength, modulus of elasticity, shear strength, and modulus of rupture of masonry composed of the compressed mud bricks made up of the selected combination was 46.43%, 97.05%, 56.40%, and 27.1% respectively as compared to the control mix. By incorporating locally available materials the mechanical properties and durability of traditional mud bricks were enhanced. This work bridges traditional mud brick composition with modern engineering insight by providing a scalable, cost-effective, environmentally friendly, application to disaster-prone and rapidly urbanizing areas worldwide.